The effect of talent management and organizational culture on employee performance with job satisfaction as a mediating variable - Syintia Mega Putri; Harif Amali Rivai; Laura Syahrul (Institute of Computer Science (IOCS), 2023)
One of the driving factors for good employee performance is Talent Management. Talent management is carried out in an effort to respond to quality company policies going forward, with talent management it is hoped that the company's performance will improve. The existence of a classification will make it easier for companies to find superior talents who will later be placed in their respective divisions. Thus this study aims to determine the effect of Talent Management and organizational culture on employee performance with job satisfaction as a mediating variable. This research was conducted at PT. Royal Family. The independent variables in this study are talent management and organizational culture and job satisfaction as mediating variables while employee performance is used as the dependent variable. Sampling technique with probability samples. So that the population of respondents used as many as 74 employees. The analytical method used is descriptive statistical analysis and inferential analysis using SmartPLS 4.0. The results of the study show that talent management has no effect on employee performance; organizational culture influences employee performance; job satisfaction affects employee performance; talent management affects job satisfaction; organizational culture affects job satisfaction; then job satisfaction as a mediating variable that does not affect talent management on employee performance; and job satisfaction as a mediating variable that influences organizational culture on employee performance.